1998
DOI: 10.1161/01.str.29.11.2363
|View full text |Cite
|
Sign up to set email alerts
|

Serum S-100 and Neuron-Specific Enolase for Prediction of Regaining Consciousness After Global Cerebral Ischemia

Abstract: Background and Purpose-The aim of our study was to assess the use of S-100 protein (S-100) and neuron-specific enolase (NSE) in serum and cerebrospinal fluid (CSF) for the prediction of patients' regaining consciousness after acute global cerebral ischemia. Methods-Sixty-four unconscious patients were followed until the return of consciousness or until death/vegetative state.Serum and CSF samples for measurement of S-100 and NSE using an immunoradiometric assay technique were obtained 24 hours (serum) and 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
0
15

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(161 citation statements)
references
References 24 publications
7
139
0
15
Order By: Relevance
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, high serum NSE levels may reflect the extent of the neuronal damage. One piece of evidence which can support this hypothesis is the relationship between the degree of neuronal damage and the serum NSE level following a cerebral stroke (Cunningham et al, 1991(Cunningham et al, , 1996DeGiorgio et al, 1995DeGiorgio et al, , 1999Fogel et al, 1997;Missler et al, 1997;Martens et al, 1998;Buttner et al, 1999;Schoerkhuber et al, 1999;Wunderlich et al, 1999) or other neuronal brain damage (DeGiorgio et al, 1995(DeGiorgio et al, , 1999Fogel et al, 1997;Martens et al, 1998; Buttner et al, 1999;Schoerkhuber et al, 1999). In these diseases, the serum NSE level exhibits a prognostic indication inasmuch as studies have found a close relationship between the volume of affected neuronal tissue and the serum NSE level (Cunningham et al, 1991(Cunningham et al, , 1996Missler et al, 1997;Wunderlich et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Plasma concentrations of the astroglial protein S-100b, a cytosolic calcium-binding protein, have been found to correlate with the extent of tissue damage (infarct volume) and neurologic outcome (6,7 ). The variations in S-100b concentrations were not significantly different within the first 6 h from stroke onset, indicating that this biomarker alone may not be sufficient for diagnosing acute stroke.…”
mentioning
confidence: 99%
“…When the brain suffers from different insults leading to impaired cellular structure and blood-brain-barrier integrity, NSE and S-100B are released quite rapidly into the cerebrospinal fluid and then into the circulation. Increased serum levels are proportionally related to the extent of cellular brain injury (Martens et al, 1998). So serum NSE and S-100B are sensitive and quantitative markers of parenchymal brain injury due to ischemia stroke, intracerebral hemorrhage, trauma and cardiopulmonary surgery (Mabe et al, 1991;Skogseid et al, 1992;Schaarschmidt et al, 1994;Isgro et al, 1997;Missler et al, 1997;Elting et al, 2000;Jonsson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%